Studi Variasi Tingkat Keanekaragaman Jenis Burung pada Berbagai Tipe Habitat di Areal Konservasi Perkebunan Sawit PT.MSM, Wilmar Plantation, Kalteng - Belinda Hastaril; Muhammad Arief Soendjoto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
High Conservation Value Areas (HCVA) in palm oil plantation is one of the efforts to reduce the negative impoct of oil palm plantations on biodiversity. The purpose of this study was to to identify bird species in dffirent types of habitats in the conserration area of oil palm plantations, calculate and compare the diversity of bird species and how is the relations with vegetation as habitat componen the study location at PT. MSM, Wilmar Plantation Central Kalimantan. The results showed the diversity value of birds and vegetation hos a positive relationship. Forested habitat v,ith heterogeneous vegetation presenting a higher value of diversity bird species than homogeneous vegetation hobitat. The highest diversity of bird species is the habitot of swampforests (H'3,70) lowland forest (H'3,69), heath forest (H'3,59) and the lowest is the habitat of palm plantatioru (H' 2,60).